The performance of Italian civil justice system: an empirical assessment - Caponi, Remo (2016)
The unreasonable length of Italian civil proceedings goes on filling pages of newspapers and magazines. According to some authoritative views, the inefficiency of the civil justice system helps explain why the Italian model legislation on civil proceedings, as well as its academic research, are not as influential on the European scene as they were in the past. It is interesting to note that an opposed thesis has pointed out that the Italian procedurallaw and recent researches in civil proceedings lack a clear, up-to-date, principle-oriented and comprehensive approach towards problems and challenges that contemporary civil justice systems face today. Such an outdated and overly complicated approach might contribute to the inefficiency of the Italian civiljustice system. The Italian Law Journal, which aims to both spread knowledge (and criticism) of the Italian legal system and foster international debate among lawyers of different traditions, may be an appropriate venue for deepening our understanding of the current performance of the Italian civil justice system. Itmay, in particular, assist in ascertaining the major causes of the inefficiencies, with a view to assessing (in a subsequent article) if the prevailing way of thinking of legal scholars may, in the end, exacerbate the relevant problems.